Challenges in scaling up testing of catalyst coated membranes for proton exchange membrane water electrolyzers - Hou, Dehua; Qiao, Geng; Liu, Liqiu; Zhang, Xiaoqiang; Yan, Yichang; Du, Shangfeng (Frontiers in Energy Research, 2025)
Prior to moving newly developed catalyst-coated membranes (CCMs) into large applications for proton exchange membrane water electrolyzers (PEMWEs), a scaling-up test is essential. However, this usually experiences a large performance drop due to the design challenges faced in the testing cell and assembly with a large active area. This work investigates a series of parameters in assembling the testing cell when scaling up the CCM from 5 cm2 to 50 cm2, including assembling force, gasket thickness, and their combination with different porous transport layers (PTLs). At an optimal assembling construction, a CCM with an active area of 5 cm2 achieves a current density of 2.4 A/cm2 at 1.8 V when tested in a 50 cm2 testing cell. In comparison, the same CCM achieves 2.2 A/cm2 when tested in a 5 cm2 testing cell. However, when scaling up to a CCM with an active area of 50 cm2, the current density drops to 1.73 A/cm2. The influence mechanisms are then explored with the assembly procedures for further improvement of the testing performance of PEM water electrolyzers.